2008
DOI: 10.1007/s00436-008-1235-6
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic control of human pathogenic parasites in aquatic ecosystems using chlorophyllin and pheophorbid as photodynamic substances

Abstract: When used at low concentrations and added to the water body, water-soluble chlorophyllin (resulting from chlorophyll after removal of the phytol) and pheophorbid (produced from chlorophyllin by acidification) are able to kill mosquito larvae and other small animals within a few hours under exposure of solar radiation. Under laboratory conditions, the use of chlorophyllin/pheophorbid as photodynamic substances for pest control in water bodies promises to be not only effective and ecologically beneficial but als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 20 publications
1
56
1
Order By: Relevance
“…However, the use of porphyrins for this purpose was only mentioned from the late 1980s of the last century [118][119][120][121]. Since then, the use of natural or synthetic porphyrin derivatives has been increasingly exploited to control and eradicate various types of insects, including pest flies capable of inducing significant damage to agricultural crops, and mosquitoes vectors of pathogens responsible for malaria (Anopheles), yellow fever (Culex, Aedes) dengue fever (Aedes) and encephalitis (Aedes, Culex, Anopheles) [46][47][48]50,[66][67][68]. Nowadays, there is a global distribution of these organisms.…”
Section: Insect Pest Eliminationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the use of porphyrins for this purpose was only mentioned from the late 1980s of the last century [118][119][120][121]. Since then, the use of natural or synthetic porphyrin derivatives has been increasingly exploited to control and eradicate various types of insects, including pest flies capable of inducing significant damage to agricultural crops, and mosquitoes vectors of pathogens responsible for malaria (Anopheles), yellow fever (Culex, Aedes) dengue fever (Aedes) and encephalitis (Aedes, Culex, Anopheles) [46][47][48]50,[66][67][68]. Nowadays, there is a global distribution of these organisms.…”
Section: Insect Pest Eliminationmentioning
confidence: 99%
“…As well as in other studies, some dark toxicity has also been observed. Other small animals, like Daphnia and fish (Chaoborus) larvae are also affected by chlorophyllin [66]. On the other hand, unlike fish larvae, more mature fish are unharmed and survive chlorophyllin treatment at concentrations, at which, for example, Culex larvae are severely affected.…”
Section: Porphyrinmentioning
confidence: 99%
“…30,31 Photodynamic chlorophyllin was capable to kill mosquito larvae and other small animals within a few hours in sunlight. 11 Recent research on chlorophyllin has been advocated by researchers. As Erzinger et al 32 demonstrated that photodynamic chlorophyllin was able to kill four different species, a small crustacean (Daphnia similis), a unicellular alga (Euglena gracilis) and two species of fish (Astyanax bimaculatus and Cyprynus carpio) which are the vector of parasitic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…14 In the presence of light chlorophyllin becomes more effective and toxic. 11,15 In recent times, it has been reported that chlorophyllin is a potent cercaricide against F. gigantica cercaria larva in sunlight. 16 Previously, it has been observed that different spectral bands of the visible light stimulate the orientation and locomotion of snails towards the light source.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier, Tripathi and Singh (2013) noted, that L. acuminata is more attracted in red light. Photodynamic chlorophyllin a derivative of chlorophyll is a potent larvicides and cercaricides (Singh and Singh, 2015;Wohllebe et al, 2009Wohllebe et al, , 2011Mahmoud et al, 2013). The aim of the present study is to explore the efficacy of photodynamic Chlorophyllin in bait formulations against both infected and uninfected L. acuminata in monochromatic visible red-light and sunlight.…”
Section: Introductionmentioning
confidence: 99%